Role of Mritika Chikitsha and Yoga Basti in Management of Asrigdar: A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Asrigdar has been characterised by excessive bleeding per vaginum. Acharya Charaka described Asrigdar as a separate disease along with its treatment in Yoni Vyapada Chikitsha Adhyaya. Acharya Charaka also described it as a Raktaja Vikara. Acharya Sushruta described Asrigdar due to Pitta Samyukt Apana Vayu. It can be correlated with Abnormal Uterine bleeding in modern. Any uterine bleeding other than normal duration, frequency and volume is considered as abnormal uterine bleeding. It affects about 30% of women in reproductive period. It is often associated with backache, pain in lower abdomen and weakness. A 23 years old female patient presented with complaints of Irregular menses with excessive bleeding per vaginum associated with pain lower abdomen. On further enquiry it was found that she had irregular menses since menarche. She took modern treatment but didn’t get significant relief. Due to excessive bleeding she had Anaemia also. Keeping all the aspects in mind a treatment has been planned. Doshas involved in Asrigdar are mainly Pitta and Vata, That is why, for Samprapti vighatan basic treatment divided into three parts i.e. Shaman chikitsha along with Sthanik chkitsha over abdomen with Krishna Mritika and Basti chikitsha. Shaman chikitsha which includes Pitta and Vata shamak, Raktastambhaka and Balya Aushadh. In Bhavprakash Nighantu Krishna Mritika has been kept in Ashtama Dhatwadi Varga and mentioned in Rakta Pradra or Rakt Vikara. The treatment protocol was followed for three cycles with positive outcome as better cycle control and symptomatic improvement in this patient.